The Utilization of Green Open Spaces in Kudus Regency to Facilitate Community Sports Activities - Dani Indrianto; Cahyo Yuwono; Ranu Baskora Aji Putra (Journal of Physical Education Health and Sport, 2025)
Community participation in sports has grown significantly. However, the effectiveness of Green Open Spaces (GOS) in meeting the community's sports needs remains unclear. This study aims to analyze and examine the availability, planning, utilization, management of open spaces, and community participation in recreational sports activities in Kudus Regency. The research employed a qualitative approach using an ethnographic design. Data were obtained from informants across all sub-districts in Kudus Regency. Data collection methods included observation, interviews, and documentation studies. Data analysis involved data collection, data reduction, data presentation, and drawing/verifying conclusions. The results showed that: 1) The availability of open spaces for sports in Kudus Regency is well-distributed across all villages in the nine sub-districts; 2) Planning for sports open spaces is in progress; however, supporting infrastructure such as parking areas and standard sports facilities still needs improvement, especially in rural areas; 3) Utilization of open spaces at the village level remains suboptimal, with more sports activities taking place in indoor sports halls (GOR) and privately managed parks. Collaboration among the government, private sector, and the community is essential to promote a healthy lifestyle through sports: 4) Regulation and control of open space use in GORs and parks are well-maintained, but at the village level, many fields are neglected and poorly maintained; 5) Community participation in sports is generally positive, influenced by environmental, social factors, available facilities, and ease of access. It can therefore be concluded that the availability of sports open spaces in Kudus Regency has been sufficiently met with well-structured development planning. However, it would be more effective if the supporting facilities were further improved, the utilization of these spaces optimized down to the village level, and community participation in sports activities continued to increase.